Toward the Right to Housing in Canada: Lived Experience, Research and Promising Practices in Deep Engagement - Malenfant, Jayne; Annan, Jes; Pin, Laura; Levac, Leah; Buchnea, Amanda (Engaged Scholar Journal)

(untitled) (University of Saskatchewan, 2024)
Canada’s 2019 Housing Strategy Act (NHSA) lays the groundwork for important advances in ensuring the right to housing for all. Two key approaches outlined in the NHSA for communities in greatest need are conducting research and providing participatory ways for those communities to shape housing rights responses. This article presents insights from a project that explored how people with lived experience of housing need and homelessness engage in research on housing precarity in Canada. We review the literature on housing precarity that features people with lived experience as research participants, applying an intersectional framework and acknowledging the settler colonial context of Canada. And, as a research team who has members with lived experiences of housing precarity, we emphasize the importance of meaningfully incorporating people’s lived experiences, seeing deep engagement as a way to advance housing rights by harnessing lived knowledges.